Transcriptomic and Physiological Analysis Reveal That α-Linolenic Acid Biosynthesis Responds to Early Chilling Tolerance in Pumpkin Rootstock Varieties - Liu, Wenqian; Zhang, Ruoyan; Xiang, Chenggang; Zhang, Ruiyun; Wang, Qing; Wang, Tao; Li, Xiaojun; Lu, Xiaohong; Gao, Shunli; Liu, Zixi; Liu, Mengshuang; Gao, Lihong; et al. (Frontiers in Plant Science, 2021)
Climate changes especially chilling stress affects cucurbit crops during winter seasonal production. Grafting to pumpkin rootstocks is widely used to improve the vigor of cucurbits, especially cucumber (Cucumis sativus L.) plants, in the face of chilling stress. In our study, multi-disciplinary aspect approaches were used to investigate growth changes of pumpkin under chilling stress. Firstly, the morphological and physiological characteristics of 14 pumpkin (Cucurbita moschata) varieties following different periods of chilling stress was analyzed by using physiological means. Mathematical results of Principle Component Analysis (PCA) with chlorophyll-a, chlorophyll-b, carotenoid contents, chilling injury index and relative electrolyte permeability indicated that relative electrolyte permeability as the primary judgment index was best associated with the comparison of chilling tolerance in pumpkin rootstock varieties. Then, transcriptomic and DCMU (Diuron) application and chlorophyll fluorescence examination analysis of pumpkin leaves revealed that 390 Cucurbita moschata differentially expressed genes (CmoDEGs) that affect photosynthesis were upregulated in leaves. 127 CmoDEGs both in leaves and roots were enriched for genes involved in unsaturated fatty acid metabolism, suggesting that plasma membrane lipids are involved in chilling perception. The results of increased composition of unsaturated fatty acid in leaves and qRT-PCR analysis of relative mRNA abundance confirmed that α-linolenic acid biosynthesis was responding to pumpkin chilling tolerance. The integration of physiological, mathematical bioinformatical and biological analysis results contributes to our understanding of the molecular mechanisms underlying chilling tolerance and its improvement in cucumber grafted on pumpkin rootstocks. It provided an important theoretical basis and reference for further understanding on the impact of climate change on plant physiological changes.